Purification and Characterization of Immunomodulatory Peptides from Hydrolysates of Thunnus albacares Dark Muscle - Cunkuan Shen; Yuanfang Xu; Jinxin Yan; Xiangyang Qi; Shaoqian Cao; Hua Yang (Foods)
Food-derived bioactive peptides have attracted considerable research interest and are increasingly utilized as functional ingredients in the food industry. In this study, the immunomodulatory peptides were isolated and purified from Thunnus albacares (T. albacares) enzymatic hydrolysates of muscles using gel chromatography and RP-HPLC, and their amino acid sequences were identified via LC-MS/MS. A total of six peptides were selected based on their affinity to toll-like receptors. Subsequently, these peptides were synthesized to confirm the immunomodulatory activities in vitro. Among all the tested peptides, two peptides, HDCDLLR and YGSVELDELGK, significantly enhanced cell proliferation and phagocytosis and increased the production of tumor necrosis factor-α (TNF-α), nitric oxide (NO), and interleukin-6 (IL-6). Molecular docking analysis indicated that these two peptides could stably bind to the receptors through hydrogen bonds and electrostatic and hydrophobic interactions. These findings suggested that peptides from enzymatic hydrolysates of T. albacares could be promising candidates for developing immunomodulatory agents in functional foods.